Successful fourth line treatment of a relapse patient with chronic hepatitis C virus infection genotype 3a using sofosbuvir, glecaprevir/pibrentasvir, and ribavirin: a case report - Bernhard, Benedikt; Stickel, Felix (Zeitschrift für Gastroenterologie, 2020)
Background Relapses after therapy with direct-acting antiviral agents (DAA) in chronic hepatitis C virus (HCV) infections are rare due to high efficacy of interferon-free therapy regimens. The presence of resistance-associated substitutions (RAS) in proteins targeted by therapy can lead to lower rates of sustained virological response (SVR) in patients receiving DAA-therapy, and little evidence exists as to how to treat these patients.Case Summary We present a case of a multi-drug-resistant HCV-genotype-3a-infection in a 50-year-old female without confirmed cirrhosis but with advanced fibrosis (liver stiffness 11.6 kPa) and low viral load. Resistance testing revealed a Y93H mutation in the NS5A gene. Therapies using sofosbuvir and daclatasvir (1st), sofosbuvir, velpatasvir and ribavirin (2nd), and subsequently with sofosbuvir, velpatasvir, and voxilaprevir (3st) did not achieve SVR. Compliance was good with rapid negativity of HCV RNA at 4 weeks of treatment on all 3 occasions. No virological breakthrough was recorded with all regimens. As a rescue attempt, the patient received 24 weeks of sofosbuvir, glecaprevir/pibrentasvir, and weight-based ribavirin at 1000 mg. With this approach, she achieved SVR but developed hepatocellular carcinoma.Conclusion The combination of sofosbuvir, glecaprevir/pibrentasvir and ribavirin could be a rescue therapy after previous relapses on DAA-therapy, especially in patients with relapse after therapy with sofosbuvir, velpatasvir, and voxilaprevir.
Keywords: chronic hepatitis C virus infection; direct-acting antiviral therapy; resistance-associated species; voxilaprevir relapse; case report